Combining the anion gap with the sequential organ failure assessment score to evaluate the short-term prognosis of patients in the cardiac intensive care unit. (1st January 2023) - Zhou, Yuan-Hang; Pang, Shuo; Miao, Guang-Rui; Zhao, Xiao-Yan; Dong, Jian-Zeng
Abstract: Background: We attempted to determine the predictive ability of the first-day Sequential Organ Failure Assessment (SOFA) score in the cardiac intensive care unit, as well as a new score combining the anion gap (AG) with the SOFA score (SOFA-AG). Methods: Information was obtained from the Medical Information Mart for Intensive Care III (MIMIC III 1.4) database. We plotted the relationship between the maximum first-day AG and 90-day mortality after admission to the care unit. Patients were divided into five groups based on the hazard ratio (HR) and assigned scores of 0, 1, 2, 3, or 4 points. We compared the area under the curve (AUC) for the receiver-operating characteristic curve of the SOFA and that of the SOFA-AG. Results: A total of 1316 patients were identified and divided into the following five groups: AG 8 to <16 mmol/L; AG 16 to <17 mmol/L; AG 17 to <19 mmol/L; AG 19 to <21 mmol/L; and AG ≥ 21 mmol/L. The SOFA-AG score had a greater AUC than the SOFA score at 7 days (0.770 vs. 0.711; P < 0.001), 14 days (0.751 vs. 0.692; P < 0.001), 28 days (0.741 vs. 0.684; P < 0.001), and 90 days (0.727 vs. 0.667; P < 0.001). Conclusions: The SOFA score showed moderate predictive value only for 7-day mortality after admission to the cardiac intensive care unit, but the SOFA-AG score had improved predictive ability for up to 90 days after admission. Highlights: Anion gap (AG) is associated with mortality of cardiac intensive care patients. The first-day Sequential Organ Failure Assessment (SOFA) score was also evaluated. Combining the AG and SOFA score significantly improved the prediction ability.